2007
DOI: 10.1371/journal.pntd.0000084
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Leishmania braziliensis Infection Following Pre-Exposure to Sandfly Saliva

Abstract: BackgroundSand fly saliva has an array of pharmacological and immunomodulatory components, and immunity to saliva protects against Leishmania infection. In the present study, we have studied the immune response against Lutzomyia intermedia saliva, the main vector of Leishmania braziliensis in Brazil, and the effects of saliva pre-exposure on L. braziliensis infection employing an intradermal experimental model.Methodology/principal findingsBALB/c mice immunized with L. intermedia salivary gland sonicate (SGS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
132
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(149 citation statements)
references
References 35 publications
15
132
0
2
Order By: Relevance
“…We (H. Louzir, IPSOS V) and others 17 formerly showed that the presence of salivary antibodies constitutes a risk factor for the development of ZCL. We, thus, focused our analysis on children who were negative for LST at the beginning of our study and who did not have any clinical evidence of previous ZCL.…”
Section: Resultsmentioning
confidence: 92%
“…We (H. Louzir, IPSOS V) and others 17 formerly showed that the presence of salivary antibodies constitutes a risk factor for the development of ZCL. We, thus, focused our analysis on children who were negative for LST at the beginning of our study and who did not have any clinical evidence of previous ZCL.…”
Section: Resultsmentioning
confidence: 92%
“…58 In contrast, L intermedia salivary gland sonicate failed to control L braziliensis infection and even increased disease progression due to low IFN-γ to IL-4 ratio. 59 These conflicting results suggest that (1) salivary gland components have the ability to change the immune response of mice by either increasing susceptibility or resistance and (2) use of sandfly saliva components may not be a suitable strategy for all strains of Leishmania. Because leishmanization seems to be an effective procedure that does not involve the sandfly, sandfly components may not be essential to the development of an effective Leishmania vaccine but may still be useful against certain strains of Leishmania.…”
Section: Sandfly Saliva Componentsmentioning
confidence: 99%
“…Anti-saliva antibodies have been associated with increased risk of CL caused by L. major, L. tropica and Leishmania braziliensis in Tunisia, Turkey and Brazil, accordingly [76,68,77]. In CL cases, anti-saliva antibodies have been shown to induce inflammation and vasculitis resulting in a greater numbers of harboring cells, especially the local neutrophils of the skin, leading to the exacerbation of the disease outcome [42].…”
Section: Sand Fly Saliva and Induction Of Immune Responses And Protecmentioning
confidence: 99%